2011
DOI: 10.1177/0145445511405185
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Outcome of a Parenting Group Curriculum: A Pilot Study

Abstract: One pressing issue facing parenting interventions for disruptive behaviors of young children is forecasting who will benefit from participation. The purpose of this study was to examine four personal and interpersonal predictors (i.e., parent depressive symptoms, parent education, coparent conflict, and marital status) of engagement (i.e., number of sessions attended) in and child outcome (i.e., problematic behavior) of a parenting group curriculum program targeting young children's disruptive behaviors. Parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 23 publications
4
9
0
Order By: Relevance
“…These effects were equivalent for maternal and paternal discipline. The lack of a significant interaction for externalizing behaviors is consistent with the only previous study to examine the association between the interaction of harsh and lax discipline and child externalizing problems (Parent et al, 2011). For youth externalizing problems, a social interactional model (e.g., Patterson, Reid, & Dishion, 1992) proposes that parental discipline exerts influence over children’s externalizing behavior through the control of reinforcing contingencies (see Forehand et al, 2013; McKee et al, 2013, for recent reviews of the intervention and non-intervention literature on parenting and youth externalizing problems).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These effects were equivalent for maternal and paternal discipline. The lack of a significant interaction for externalizing behaviors is consistent with the only previous study to examine the association between the interaction of harsh and lax discipline and child externalizing problems (Parent et al, 2011). For youth externalizing problems, a social interactional model (e.g., Patterson, Reid, & Dishion, 1992) proposes that parental discipline exerts influence over children’s externalizing behavior through the control of reinforcing contingencies (see Forehand et al, 2013; McKee et al, 2013, for recent reviews of the intervention and non-intervention literature on parenting and youth externalizing problems).…”
Section: Discussionsupporting
confidence: 88%
“…Permissive parents, who were originally described by Baumrind (1968) as tending to avoid behavioral control or failing to set limits and enforce rules, are also more likely to have children and adolescents with both externalizing (e.g., Dishion, Patterson, Stoolmiller, & Skinner, 1991; Hanisch, Hautmann, Pluck, Eichelberger, & Dopfner, 2014; Lansford et al, 2014; Parent, Forehand, Merchant, Long, & Jones, 2011) and internalizing (e.g., Akhter, Hanif, Tariq, & Atta, 2011; Williams et al, 2009) problems. The second component of lax discipline, inconsistency, has been operationalized as the lack of follow-through in maintaining and adhering to rules for children's behavior (Melby et al, 1998; Shelton, Frick, & Wootton, 1996) or giving in to coercive child behavior (Arnold et al, 1993).…”
mentioning
confidence: 99%
“…First, we note that maternal engagement was unrelated to the Pretest scores for the outcomes, and thus, the significant effects of the intervention cannot be explained by any pre-existing differences among the mothers. Second, married mothers and those with fewer children were more engaged in child-oriented play and delivered higher doses of it to their toddlers than unmarried mothers and those with more children, consistent with the extant evidence (Parent et al, 2011; Reyno & McGrath, 2006). Perhaps competing hardships leave unmarried mothers and those with several children with insufficient internal resources to fully commit to the intervention.…”
Section: Discussionsupporting
confidence: 75%
“…Nix et al (2009) found that parents who faced more challenges in their lives were less likely to show high-quality engagement, which in turn led to worse outcomes. Parent, Forehand, Merchant, Long, and Jones (2011) found that marital status predicted engagement, with married parents (mostly mothers) more engaged than those who were single. Therefore, we tested a structural equation model in which factors such as mothers’ race, financial resources, the amount of recent life stress, marital status, and the number of children were considered the predictors of maternal engagement -- or the dose of the intervention delivered to the child – and where the dose was considered a mediator of the potential links between those factors and the effects of the intervention.…”
mentioning
confidence: 96%
“…Furthermore, parents who report their children are above the clinical cutoff in disruptive behaviors also report higher levels of overreactive discipline and, to some extent, lax parenting. Participating in a community-based parenting intervention can be associated not only with increases in appropriate parenting skills and decreases in child disruptive behaviors but positive changes in parent depressive symptoms and coparent conflict Parent et al 2011). These findings are compatible with findings for clinicreferred samples (see McMahon and Forehand 2003, for a review).…”
Section: Discussionsupporting
confidence: 68%